Slow Instillation of Cooled Lignocaine Gel: Does it Reduce Urethral Discomfort During Cystoscopy? - Basnet, Robin Bahadur; Shah, Arvind Kumar; Shah, Chitaranjan (Nepalese Medical Journal, 2019)
Introduction: Intraurethral instillation of 2% lignocaine hydrochloride is associated with discomfort and stinging sensation, especially to male patients. This study was aimed to determine whether slow instillation and cooled gel reduce this discomfort. Materials and Methods: A prospective randomized study was done comparing initial and procedural discomfort between 2% lignocaine instilled at room temperature and cooled to 4° C, and that instilled over 2 seconds and 10 seconds. Hundred and sixty male patients were divided into two groups of eighty each for the two studies. Results: Significant reduction in initial discomfort was observed with 10ml of 2% lignocaine hydrochloride cooled to 4° C and also when instilled over 10 seconds. Although procedural discomfort was also lesser in these two sets, it was not statistically significant. Conclusions: Discomfort, the most common complaint of male patients during rigid cystoscopy, can be reduced by slow instillation of lignocaine hydrochloride gel and also if the gel is cooled to 4° C.